A saúde bucal na saúde da família : ação comunicativa de Habermas guiando as relações - Esposti, Carolina Dutra Degli (2007)
The study analyses the insertion of dentists into the Family Health Program (FHP) multidisciplinary team. It also characterises the work process of dentists with regards to the team work and identifies possible communicative approaches and consensus between the team professionals. The theoretical foundation was built from studies about team work relations, and more specifically from Habermas’ Theory of Communicative Action. It consists of an exploratory case study, with a qualitative approach, carried out at Vitoria, capital city of Espírito Santo State, Brazil. The research focused on 14 workers from two Health Family Teams (HFT) and Oral Health Team (OHT) (doctor, nurse, nurse assistant, community health worker, dentist, dental hygienist and dental assistant) who work at the Health Family Units of Maruípe and Ilha do Principe. The data was collected through participant observation and semi-structured recorded interview. The empirical material was analysed through content analysis and the discourses were related to the authors who support the study. The results show the difficult integration between dentists and the other team members, especially due to their lack of skills to perform in multi-professional teams, since they keep hierarchic and individualised ways of working, focusing on clinical procedures and hard technologies, which characterises hegemonic model of practicing dentistry. Adding to that, there is great pressure from management towards increased productivity, ratio of one OHT to two HFT, lack of good work conditions, temporary employment contracts that leads to high staff turnover, lack of responsibility, inappropriate undergraduate education, poorly prepared professionals who are not trained to work in a team environment and to follow the FHP’s guidelines. All these facts were seen as limitations for the team interaction. The insertion of oral health in the FHP not only improved the access to dental services but also created a possibility to change the traditional model of practicing dentistry. In order to consolidate the FHP as the model of Primary Health Care in Brazil, the relationship between dentists and the other health professionals should follow the Habermas Communicative Action, where at least two subjects use linguistic communication to build common action plan, through consensus. This action plan must aim the needs of the users and their life conditions.